Kritik Sastra Arab Pada Masa Jahilyah - Hafizh Qurrota Ayun (‘A Jamiy : Jurnal Bahasa dan Sastra Arab, 2022)
This study discusses the phenomenon of Arabic literary criticism that occurred during the period of ignorance. By knowing the critical phenomena that existed during the jahiliyyah period, it will be known how the character of Arabic literary criticism at that time was. Literary criticism during the jahiliyyah period was still very simple, namely by determining good and bad or comparing works with one another based on their natural literary taste. The result can be seen in the phenomenon of Muallaqa>t in which some of the best poems from various tribes are placed. The forms of literary criticism during the jahiliyyah period were generally in four forms, namely linguistic criticism, meaning criticism, musical criticism, and poet strata criticism. Linguistic criticism is criticism of the misuse of language. Meaning criticism is a criticism that judges the merits of a poem in terms of meaning. There are three basics in the critique of its meaning, namely its relevance to the life of the Arab community, the compatibility between the word and the meaning that shows it, and the aesthetic value or beauty of the meaning contained in the poem. Musical criticism is literary criticism seen from the good or bad standards of arud that exist in poetry. Criticism of the poet's strata is criticism based on the level of the poet during the jahiliyyah period.